Garantia da Qualidade na Indústria de Produtos de Origem Animal. - Silva, Victor Hugo de Melo da (Universidade Federal do Tocantins, 2023)
The search for an innocuous food is indispensable as much economically and socially. Quality assurance begins in the field, through the Food Industry until it reaches the consumer's table. In this way the industry must follow hygienic-sanitary standards to provide a final product that meets the criteria of the legislation. The general objective of the work was address the main Quality Tools that act in the control procedures in the establishments handling products of animal origin, such as, Hazard Analysis and Critical Control Points (HACCP), Good Manufacturing Practices (GMP), Standard Procedures of Operational Hygiene (PPHO) and Self-Control Programs. Report activities carried out during the period of Mandatory Supervised Curricular Internship, March 13 to May 25, 2023, at the State Inspection Service governed by the Agricultural Defense Agency in Araguaína - Tocantins, as well as quantify the fiscal actions carried out in two companies in the food industry, in the months of January to April 2023.